Global research trends in atherosclerosis: A bibliometric and visualized study - Tian, Wende; Zhang, Tai; Wang, Xinyi; Zhang, Jie; Ju, Jianqing; Xu, Hao (Frontiers in Cardiovascular Medicine, 2022)
Background: Increasing evidence has spurred a considerable evolution of concepts related to atherosclerosis, prompting the need to provide a comprehensive view of the growing literature. By retrieving publications in the Web of Science Core Collection (WoSCC) of Clarivate Analytics, we conducted a bibliometric analysis of the scientific literature on atherosclerosis to describe the research landscape. Methods: A search was conducted of the WoSCC for articles and reviews serving exclusively as a source of information on atherosclerosis published between 2012 and 2022. Microsoft Excel 2019 was used to chart the annual productivity of research relevant to atherosclerosis. Through CiteSpace and VOSviewer, the most prolific countries or regions, authors, journals, and resource-, intellectual-, and knowledge-sharing in atherosclerosis research, as well as co-citation analysis of references and keywords, were analyzed. Results: A total of 20,014 publications were retrieved. In terms of publications, the USA remains the most productive country (6,390, 31,93%). The most publications have been contributed by Johns Hopkins Univ (730, 3.65%). ALVARO ALONSO produced the most published works (171, 0.85%). With a betweenness centrality of 0.17, ERIN D MICHOS was the most influential author. The most prolific journal was identified as Atherosclerosis (893, 4.46%). Circulation received the most co-citations (14,939, 2.79%). Keywords with the ongoing strong citation bursts were “nucleotide-binding oligomerization (NOD), Leucine-rich repeat (LRR)-containing protein (NLRP3) inflammasome”, “short-chain fatty acids (SCFAs)”, “exosome”, and “homeostasis”, etc. Conclusions: The research on atherosclerosis is driven mostly by North America and Europe. Intensive research has focused on the link between inflammation and atherosclerosis, as well as its complications. Specifically, the NLRP3 inflammasome, interleukin-1β, gut microbiota and SCFAs, exosome, long non-coding RNAs, autophagy, and cellular senescence were described to be hot issues in the field. Keywords: atherosclerosis, inflammation, immunology, bibliometrics, hotspots